Japanese direct foreign investment : - Kojima, Kiyoshi (Charles E. Tutte company, 1978)
Direct foreign investment and the activities of multinational corporations are new dynamic elements in the international economy. This book identifies, theoretically and practically, a Japanese model of multinational business operations which has characteristics differing from the American or "anti-trade oriented" type, and casts light on important policy implications concerning direct foreign investment and multinational corporations. By developing a macroeconomic approach to direct foreign investment, instead of the prevalent explanation from the viewpoint of business administration and industrial organisation, this study adds to current knowledge of the multinational corporation. It endeavours to bridge the gap of separated treatments between international trade and foreign investment, and presents an integrated theory from the viewpoint of a dynamic reorganisation in the international division of labour. The book also includes two introductory surveys on the survey of international division of labour and foreign investment.